IN-SITU ELEMENTAL DETECTION IN TOBACCO AND ASH BY LASER INDUCED BREAKDOWN SPECTROSCOPY: IMPLICATIONS FOR HUMAN HEALTH AND ENVIRONMENTAL SUSTAINABILITY - Nimra Shahzad; Madma Habib; Yasir Ali (Spectrum of Engineering Sciences, 2025)
Laser induced breakdown spectroscopy (LIBS) is a versatile technique that is used to determine elemental composition in different samples. It is simple and fast multi-elemental analysis technique which provides potential tool in situ chemical analysis with high resolution, better limit of detection (LOD) and is cost efficient. Smoking tobacco in cigarettes amplifies the risk of growing certain diseases such as cancer, heart disease, stroke, lung diseases, diabetes, and chronic obstructive pulmonary disease (COPD), which includes emphysema and chronic bronchitis. About 80% of lung cancer as well as about 80% of all lung cancer deaths are due to smoking. Smoking tobacco is a considerable source of consuming several harmful and toxic elements that are unhealthy for human body. The presence of some toxic elements causes serious health concern to active as well as to passive smokers. In the present study, we employ LIBS technique to identify and detect toxic and harmful elements in tobacco and ash from four popular Pakistani cigarette brands, ensuring human health protection, agricultural safety, and environmental sustainability. The Q-switched ND: YAG (neodymium-doped yttrium aluminum garnet) laser (λ=1064 nm) with laser energy 90 mJ and pulse duration 10 ns were used to ablate the samples. From the recorded optical emission spectra of these samples several elements were detected (Fe, Ca, Mn, Sc, Ti, Cr, Sc, Sr and Ni) among which Chromium Cr, Nickel Ni and Strontium Sr are highly toxic elements. Furthermore, the presence of toxic and heavy metals in ash could be significant contributor to metal load in soil as well as for human body. We calculated the electron temperature (Te) by the Boltzmann Plot Method from the spectroscopic analysis of the transition lines of Fe-I (iron). Stark Broadening Method was used to determine electron number density (Ne) from the transition line of Fe-I at 422.413 nm and 649.25 nm for tobacco and ash sample respectively, under the assumption of local thermodynamic equilibrium. The present results demonstrate that LIBS is a powerful diagnostic tool for effectively tracing harmful and toxic elements in various solid samples, facilitating the development of protective environmental measures.